DETEKSI FORMALIN PADA TAHU YANG DIJUAL DI PASAR TRADISIONAL KOTA GORONTALO MENGGUNAKAN EKSTRAK UBI JALAR UNGU - khosidah, waridatul; malaha, adnan; AR Lainjong, Erfan (LPPM Universitas Bina Mandiri Gorontalo, 2023)
Formalin is a chemical whose use is prohibited for food products.Formalin with its trade name is formaldehyde in water with a content of 30-40%. Formaldehyde contamination in foodstuffs is very harmful to the body. Formaldehyde can cause cancer of the respiratory tract and increase the risk of leukemiaThis study aims to determine the presence or absence of formalin content in tofu using purple sweet potato extract which was carried out using the maceration extraction method.Natural ingredients containing anthocyanins can be used as an alternative to formalin testing. This study used a qualitative research method using purple sweet potato extract as an inspection indicator because it contains anthocyanin which is capable of detecting the presence of formaldehyde in tofu by means of a color change reaction.anthocyanin which is amphoteric in nature which has the ability to react well with acidic and basic pH, if in an acidic medium the anthocyanin will turn red. Formalin is acidic, so when anthocyanin meets formalin it will produce a red color that is increasingly concentrated. Meanwhile, if the anthocyanin pigment does not change color to red or remains in its original color, then it does not contain formalin. Anthocyanins will change color as the pH value changes The results showed that the 19 tofu samples tested were declared negative as indicated by the absence of a reddish-blue discoloration reaction.